Bone Scintigraphy After a Negative Radiological Skeletal Survey Improves the Detection Rate of Inflicted Skeletal Injury in Children - Blangis, Flora; Poullaouec, Cyrielle; Launay, Elise; Vabres, Nathalie; Sadones, Flavie; Eugène, Thomas; Cohen, Jérémie F.; Chalumeau, Martin; Gras-Le Guen, Christèle (Frontiers in Pediatrics, 2020)
Background Timely diagnosis of child physical abuse is of paramount importance. The added value of bone scintigraphy (BS) after a negative radiological skeletal survey (RSS) in children with suspected physical abuse has never been evaluated. Objective To assess the extent to which BS could improve the detection rate of skeletal injury in children with suspected physical abuse with an initial negative RSS. Methods We used discharge codes to retrospectively identify children evaluated for suspected physical abuse in a University hospital (Nantes, France). We included all consecutive children younger than 3 years old who underwent both RSS and BS, with an interval between tests of ≤ 96 hr, from 2013 to 2019. BS and RSS results were interpreted independently during the study period. We specifically analysed BS results for children with a negative RSS to assess the value of BS as an add-on test. Results Among the 268 children ≤ 3 years old with suspected physical abuse who underwent RSS, 140 (52%) also underwent BS within 96 hr and were included in the analysis. The median age was 6 months (interquartile range: 3-8). The detection rate of ≥ 1 skeletal injury with RSS alone was 49% (n=69/140; 95%CI 4-58%) versus 58% (n=81/140; 50-66%) with RSS followed by add-on BS, for an absolute increase in detection rate of 9 percentage points (4-14). The number of children with a negative RSS who would need to undergo BS to detect one additional child with ≥ 1 skeletal injury was 6 (4-11). Conclusion In young children with suspected physical abuse with a negative RSS, add-on BS would allow for a clinically significant improvement in the detection rate of skeletal injuries, for a limited number of BS procedures required. Prospective multicenter studies are needed to confirm these findings.